Pattern recognition applications and methods : 5th International Conference, ICPRAM 2016, Rome, Italy, February 24-26, 2016, Revised selected papers /: 5th International Conference, ICPRAM 2016, Rome, Italy, February 24-26, 2016, Revised selected papers. (2017) - Unknown
No abstract available